PPARβ/δ upregulates the insulin receptor β subunit in skeletal muscle by reducing lysosomal activity and EphB4 levels - Jue-Rui Wang; Javier Jurado-Aguilar; Emma Barroso; Ricardo Rodríguez-Calvo; Antoni Camins; Walter Wahli; Xavier Palomer; Manuel Vázquez-Carrera (Cell Communication and Signaling)
Abstract Background The increased degradation of the insulin receptor β subunit (InsRβ) in lysosomes contributes to the development of insulin resistance and type 2 diabetes mellitus. Endoplasmic reticulum (ER) stress contributes to insulin resistance through several mechanisms, including the reduction of InsRβ levels. Here, we examined how peroxisome proliferator-activated receptor (PPAR)β/δ regulates InsRβ levels in mouse skeletal muscle and C2C12 myotubes exposed to the ER stressor tunicamycin. Methods Wild-type (WT) and Ppard −/− mice, WT mice treated with vehicle or the PPARβ/δ agonist GW501516, and C2C12 myotubes treated with the ER stressor tunicamycin or different activators or inhibitors were used. Results Ppard −/− mice displayed reduced InsRβ protein levels in their skeletal muscle compared to wild-type (WT) mice, while the PPARβ/δ agonist GW501516 increased its levels in WT mice. Co-incubation of tunicamycin-exposed C2C12 myotubes with GW501516 partially reversed the decrease in InsRβ protein levels, attenuating both ER stress and the increase in lysosomal activity. In addition, the protein levels of the tyrosine kinase ephrin receptor B4 (EphB4), which binds to the InsRβ and facilitates its endocytosis and degradation in lysosomes, were increased in the skeletal muscle of Ppard −/− mice, with GW501516 reducing its levels in the skeletal muscle of WT mice. Conclusions Overall, these findings reveal that PPARβ/δ activation increases InsRβ levels by alleviating ER stress and lysosomal degradation.